2014
DOI: 10.1016/j.toxlet.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic view of polybrominated diphenyl ether (PBDE) developmental neurotoxicity

Abstract: Polybrominated diphenyl ethers (PBDEs), extensively used in the past few decades as flame retardants in a variety of consumer products, have become world-wide persistent environmental pollutants. Levels in North America are usually higher than those in Europe and Asia, and body burden is 3 to 9-fold higher in infants and toddlers than in adults. The latter has raised concern for potential developmental toxicity and neurotoxicity of PBDEs. Experimental studies in animals and epidemiological observations in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
145
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(151 citation statements)
references
References 211 publications
(317 reference statements)
5
145
0
1
Order By: Relevance
“…Previous studies have reported that the PBDEs are toxic to the liver activity (Zhou et al, 2002), thyroid and reproduction systems (Yu et al, 2015), nervous system (Costa et al, 2014) and immune system (Lv et al, 2015). Though some highly-toxic PBDEs have been banned in many countries, other PBDEs with relatively lower toxicity, such as BDE-209, are still largely produced and used in the world (Chen et al, 2012;Akortia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the PBDEs are toxic to the liver activity (Zhou et al, 2002), thyroid and reproduction systems (Yu et al, 2015), nervous system (Costa et al, 2014) and immune system (Lv et al, 2015). Though some highly-toxic PBDEs have been banned in many countries, other PBDEs with relatively lower toxicity, such as BDE-209, are still largely produced and used in the world (Chen et al, 2012;Akortia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a declining trend in the levels of PBDEs observed in certain regions, this group of persistent pollutants is still detectable in various environmental media and biotic samples (Baron et al, 2015;Hassan et al, 2013;Yu et al, 2016;Zheng et al, 2015). It has been demonstrated that PBDEs adversely affect the developing brain, resulting in neurodevelopmental disorders (Costa et al, 2014(Costa et al, , 2016Kodavanti et al, 2015). However, there is little understanding of the accumulation of PBDEs in the brain and their transfer across the blood-brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%
“…such as reproductive and developmental effects, neurobehavioral toxicity and thyroid hormone disruption (Dingemans et al, 2011;Costa et al, 2014;Guyot et al, 2014;Buratovic et al, 2014). Decabromodiphenyl ether (BDE209), which is the principal component of commercial PBDEs, comprises approximately 80% of the world market demand for PBDEs (de Wit, 2002).…”
Section: Introductionmentioning
confidence: 99%